GyrB vs. 16s rRna sequencing for the identification of Campylobacter jejuni, Campylobacter coli, and Campylobacter lari (Journal of Nucleic Acids Investigation, 2011)
Species of the genus Campylobacter are responsible for the largest number of bacterial food-borne illness cases occurring yearly in the developed world. The majority of disease is caused by three of the thermotolerant Campylobacter species: Campylobacter jejuni, Campylobacter coli, and Campylobacter lari. An inability to differentiate these three species using the commonly employed 16S rRNA sequencing procedure has led to the development of alternative methods to identify these bacteria. Some of these methods include the utilization of the gyrB gene. A reliable method was developed for the differentiation of C. jejuni, C. coli, and C. lari employing the gyrB gene. It involves amplification and sequencing of a species-variable region of the gene with a single pair of DNA primers. The method works well for the separation and organization of the three Campylobacter strains as well as satisfying the suggested guidelines for sequence based identification for most strains investigated.